Opposing Extremes of Zygomatic Bone Morphology: Australopithecus Boisei versus Homo Neanderthalensis. Issue 1 (January 2017) - Rak, Yoel; Marom, Assaf
ABSTRACT: The lateral margin of the zygomatic bone of Australopithecus boisei flares both anteriorly and laterally. As a result, the bone loses the suspensory bracing of the facial frame and is transformed into a visor‐like structure that supports itself and gains its rigidity from its shape. The coronally oriented bony plates and the outline of the facial mask help the A. boisei face resist the effect of the visor‐like structure, which tends to pull the bone plates of the face away from the midline. On the other hand, the nearly sagittal orientation of the zygomatic bone in Homo neanderthalensis helps the face resist torque and bending forces, which themselves stem from the positioning of the bite point on the anterior teeth. Although the zygomatic bones of these two taxa are highly specialized, they differ fundamentally from each other. Anat Rec, 300:152–159, 2017. © 2016 Wiley Periodicals, Inc.